O usuário da Defensoria Pública : seus vínculos com a instituição e com os equipamentos público-comunitários - Párraga, Maria Beatriz Bastos (2019)
The Public Defender's Office of the State of Mato Grosso (DPEMT), supported by complementary law 132/2009, operates with the mission of guiding, promoting and defending rights at all levels, judicial and extrajudicial, of individual or collective interests free of charge to those in need. Therefore, it has an interdisciplinary service that, in several cases, directs the users to other establishments to search for resolution of their demands. It is observed that many of DPEMT users remain for a long time being accompanied in their procedural steps and they return frequently requesting to listen to their demands, demonstrating a strong link with the institution, in order to seek support for questions that will go beyond the legal scope because they cover diverse conflicts. This study investigates the links formed between the DPEMT user, the concrete institution Defensoria and the abstract institutions that are updated there. It also considers users‘ roaming by other public-community equipment involved in this relationship and the psychic dynamics established between subject-institution. During four months of 2018, occurred the monitoring of eleven users in their attendances experienced both in the Defensoria itself and in other establishments to which they were referred through it. The purpose was to accompany the users with routine appointments and to learn what they understood about the Public Defender‘s office and it they sought, accompaniments that gave information about aspects of the reality of this users that subsidized the reflections presented here about their perceptions and about the object relation created. This study was based on the psychoanalytic approach, especially in Melanie Klein‘s references to object relations and Pichon-Rivière, in relation to his concept of bond. The collection of data, comprised of two moments, the first performed through a series of records in field journals based on the observations of the appointments, and later by an open, individual interview, carried out at the end of the follow-up of the participants. The analysis of the collected data covered five of the eleven users and performed and guided by an psychoanalytic interpretation of the scenes and the speeches, expresses the debate of a series of clinical-conceptual aspects, betting on the reading of the complexity of the bond as a dynamic structure, which manifests itself internally and externally, composed of a psychosocial, socio dynamic and institutional dimension that calls attention to the context and the group to which the users belong. In the analysis of the data, it was emphasized the existence of multiple links in established relationships, the complexity of the concept was resumed and the ambivalent (or bivalent Pichon-Rivière ties) and paradoxical relations between dependence and autonomy were evident. It also tried to punctuate particular subjective, universal and unique elements experienced and shared by the users in the contacts with the institution.